Trends in Adult Chlamydia and Gonorrhea Prevalence, Incidence and Urethral Discharge Case Reporting in Morocco over 1995–2015—Estimates Using the Spectrum-Sexually Transmitted Infection Model. Issue 9 (September 2017) - El-Kettani, Amina; Mahiané, Guy; Bennani, Aziza; Abu-Raddad, Laith; Smolak, Alex; Rowley, Jane; Nagelkerke, Nico; El-Rhilani, Houssine; Alami, Kamal; Hançali, Amina; Korenromp, Eline
Abstract : Background: Evolving health priorities and resource constraints mean that countries require data on sexually transmitted infections (STI) trends to inform program planning and resource allocation. Methods: The Spectrum modeling tool estimated prevalence and incidence of gonorrhea and chlamydia in Morocco's 15- to 49-year-old population, based on prevalence surveys. Incident cases, broken down between symptomatic and asymptomatic, and treated versus untreated, were compared with urethral discharge (UD) case reports, to estimate reporting completeness among treated UD cases. Results: Gonorrhea prevalence was estimated at 0.37% (95% confidence interval [CI], 0.14–1.0%) in women and 0.32% (0.12–0.87%) in men in 2015; chlamydia prevalences were 3.8% (95% CI, 2.1–6.4%) and 3.0% (95% CI, 1.7–5.1%). Corresponding estimated numbers of new cases in women and men in 2015 were 79, 598 (95% CI, 23, 918–256, 206) and 112, 013 (95% CI, 28, 700–307, 433) for gonorrhea, and 291, 908 (95% CI, 161, 064–524, 270) and 314, 032 (95% CI, 186, 076–559, 133) for chlamydia. Gonorrhea and chlamydia prevalence had declined by an estimated 41% and 27%, respectively, over 1995 to 2015. Prevalence declines probably related to improved STI treatment coverage, and decreasing risk behaviors. Reporting completeness among treated UD cases was estimated at 46% to 77% in 2015. Reported UD cases corresponded to 13% of all estimated (symptomatic and asymptomatic) gonorrhea and chlamydia cases. Conclusions: STI declines and improvements in treatment coverage are consistent with Morocco's introduction of syndromic management in 2000, scale-up of prevention, and declining human immunodeficiency virus incidence. While gonorrhea is four-fold more common as cause of clinical UD cases than chlamydia, Morocco continues to suffer a large, untreated burden of chlamydia. Reliable monitoring of both STIs requires new periodic surveys and/or novel forms of affordable surveillance beyond high-risk populations. Abstract : Trend estimations using the Spectrum-sexually transmitted infection (STI) model based on survey and surveillance data from Morocco showed declining gonorrhea and chlamydia prevalence and incidence in adults over 1995 to 2015. Supplemental digital content is available in the text.